Analysis of Energy Management System with Connected DC Micro Grid: Optimizing energy management in a connected DC microgrid system (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Microgrid is the combination of distributed energy resources (DER), distributed storage (DS) and load. The growing need of electrical energy can be fulfilled by harnessing energy from renewable energy sources (RES) along with conventional sources of energy. By understanding need of electricity and available energy sources and storage, energy management can be done. The task of Energy Management System (EMS) is to manage the energy between source and load. Micro grids are able to integrate distributed renewable energy, take advantage of renewable sources, provide higher power reliability, reduce electricity transmission loss, and decrease greenhouse gas emissions. The study considers solar power, wind power, fuel cell generators, power storage and electricity demand in micro grid system. An optimization model of the micro grid system is proposed and the optimal operating strategy of the system is presented.